2020
DOI: 10.1002/aur.2270
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Influences Between Parent Input and Child Language Skills in Dyads Involving High‐ and Low‐Risk Infants for Autism Spectrum Disorder

Abstract: We examined the language input of parents of infants at high and low familial risk for autism spectrum disorder (ASD) and investigated reciprocal associations between parent input and child language skills in the first 2 years of life. Parent‐infant dyads (high‐risk: n = 53; low‐risk: n = 33), 19 of whom included an infant later diagnosed with ASD, were videotaped during free play interactions at 12, 18, and 24 months. Measures of parent input were derived from parent–child interactions. Children's language sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 63 publications
3
52
5
Order By: Relevance
“…Subtle group differences in caregiver speech may also emerge as high-risk infants display difficulties with the development of social-communicative skills. Choi et al (Choi, Nelson, Rowe, & Tager-Flusberg, 2020) found that parents of high-risk infants and low-risk parents used similarly complex sentences when speaking to their 12-month-old infants, but high-risk parents used sentences with simpler complexity when speaking to their 18-month-old infants. It may be the case that parents of high-risk infants adjust their language to match their infant's communication skills (Choi et al, 2020).…”
Section: Caregiver Speech and The Home Language Environment In Infantmentioning
confidence: 99%
“…Subtle group differences in caregiver speech may also emerge as high-risk infants display difficulties with the development of social-communicative skills. Choi et al (Choi, Nelson, Rowe, & Tager-Flusberg, 2020) found that parents of high-risk infants and low-risk parents used similarly complex sentences when speaking to their 12-month-old infants, but high-risk parents used sentences with simpler complexity when speaking to their 18-month-old infants. It may be the case that parents of high-risk infants adjust their language to match their infant's communication skills (Choi et al, 2020).…”
Section: Caregiver Speech and The Home Language Environment In Infantmentioning
confidence: 99%
“…However, this study combined infants later diagnosed with autism and infants who did not go on to receive a diagnosis. Some studies have shown longitudinal associations between linguistic mapping and autistic children's later language [Choi, Nelson, Rowe, & Tager‐Flusgerg, 2020; Dimitrova, Özçalışkan, & Adamson, 2016; Haebig et al, 2013b], but these associations have not held up when potential confounding variables were taken into account [Haebig et al, 2013b], or when measured over a period shorter than 1 year [McDuffie & Yoder, 2010] or longer than 1 year [Haebig et al, 2013a]. However, Choi et al [2020] found associations in the reverse direction.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown longitudinal associations between linguistic mapping and autistic children's later language [Choi, Nelson, Rowe, & Tager‐Flusgerg, 2020; Dimitrova, Özçalışkan, & Adamson, 2016; Haebig et al, 2013b], but these associations have not held up when potential confounding variables were taken into account [Haebig et al, 2013b], or when measured over a period shorter than 1 year [McDuffie & Yoder, 2010] or longer than 1 year [Haebig et al, 2013a]. However, Choi et al [2020] found associations in the reverse direction. They coded instances where caregivers responded to semantic aspects of children's communication (e.g., after the child points to a toy, the caregiver says “you see the toy!”; a construct similar to linguistic mapping), and found that autistic children's language abilities predicted caregivers' later contingent responses in a model controlling for several parent and child factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations